Experiences of tobacco smoking and quitting in smokers with and without chronic obstructive pulmonary disease-a qualitative analysis. Issue 1 (December 2015) - van Eerd, Eva; Risør, Mette; van Rossem, Carolien; van Schayck, Onno; Kotz, Daniel
Abstract Background Smokers with chronic obstructive pulmonary disease (COPD) seem to be a special subgroup of smokers that have a more urgent need to quit smoking but might find it more difficult to do so. This study aimed to explore which justifications for tobacco smoking and experiences of quitting were commonly shared in smokers with and without COPD, and which, if any, were specific to smokers with COPD. Methods In ten primary healthcare centres in the Netherlands, we conducted semi-structured, in-depth interviews in 10 smokers with and 10 smokers without COPD. Results Three themes were generated: 'balancing the impact on health of smoking', 'challenging of autonomy by social interference', 'prerequisites for quitting'. All participants trivialized health consequences of smoking; those with COPD seemed to be less knowledgeable about smoking and health. Both groups of smokers found autonomy very important. Smokers with COPD were indignant about a perceived lack of empathy in their communication with doctors. Furthermore, smokers with COPD in particular had little faith in the efficacy of smoking cessation aids. Lastly, motivation for quitting was dominated by fluctuation and smokers with COPD specifically maintained that their vision of life was linked with quitting. Conclusions The participants showed many similarities in their reasoning about smoking and quitting. The corresponding themes argue for a less paternalistic regime in the communication with smokers with attention required for the motivational stage and room made for smokers' own views, and with clear information and education. Furthermore, addressing social interactions, health perceptions and moral agendas in the communication with smokers with COPD may help to make smoking cessation interventions more suitable for them.